Social factors associated with poverty in households in Peru - Quispe Mamani, Julio Cesar (2022)
The objective of the research was to identify the determinants of poverty at the household level in Peru in 2020. The research design was descriptive and correlational, with a type of nonexperimental research and quantitative approach, and considered the logit econometric model; the sources of information used correspond to the National Household Survey of the National Institute of Statistics and Informatics, from which the variables that are considered determinants of poverty were extracted and managed. It was determined that the size of the household positively influences by 1.3%; the economic income of the head of household negatively influences by 0.000828%; the years of education of the head of household influences by 0.1%; homeownership influences by 0.9%; access to social programs of food and non-food aid influence by 0.9% and 0.6%, respectively; access to drinking water service, hygienic service and electric power service have a negative influence of 1.8%, 0.6% and 1.7%; all these factors are associated with the poverty of households in Peru. Therefore, the social determinants of poverty were household size, economic income, years of education, access to homeownership, access to a social food aid program, access to a social non-food aid program, access to drinking water services, access to hygienic services and access to electric power services.